1986
DOI: 10.1002/ana.410200206
|View full text |Cite
|
Sign up to set email alerts
|

Selective saccadic palsy caused by pontine lesions: Clinical, physiological, and pathological correlations

Abstract: Two patients suffered a selective deficit of voluntary saccades and quick phases of nystagmus after hypoxic-ischemic insults during open-heart surgery. All voluntary saccades, in both horizontal and vertical planes, were slow, and quick phases of vestibular and optokinetic nystagmus were absent. Smooth pursuit, the vestibuloocular reflex, the ability to hold steady eccentric gaze, and vergence eye movements were all preserved. Pathological studies in 1 patient confirmed neuronal necrosis and gliosis, consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
2

Year Published

1992
1992
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 22 publications
1
34
2
Order By: Relevance
“…Leigh & Tomsak (2004) postulated that a bilateral infarction of the frontal and parietal eye fields would cause impairment of all voluntary eye movements (saccades, pursuit, vergence) with preservation of reflexive eye movements (slow and quick phases of vestibular and optokinetic nystagmus). However, in our patient and in other cases (Bernat and Lukovits, 2004;Tomsak, Volpe, Stahl, and Leigh, 2002;Hanson et al, 1986), rapid eye movements (reflex quick phases and voluntary saccades) were abolished while pursuit and vestibular movements were abnormal but not absent. These patients most likely have focal, paramedian brainstem infarction (Leigh and Tomsak, 2004), although MRI in these patients, including ours, showed no evidence a lesion in this region, perhaps because of resolution limitations related to cellular-level dysfunction.…”
Section: Discussioncontrasting
confidence: 50%
“…Leigh & Tomsak (2004) postulated that a bilateral infarction of the frontal and parietal eye fields would cause impairment of all voluntary eye movements (saccades, pursuit, vergence) with preservation of reflexive eye movements (slow and quick phases of vestibular and optokinetic nystagmus). However, in our patient and in other cases (Bernat and Lukovits, 2004;Tomsak, Volpe, Stahl, and Leigh, 2002;Hanson et al, 1986), rapid eye movements (reflex quick phases and voluntary saccades) were abolished while pursuit and vestibular movements were abnormal but not absent. These patients most likely have focal, paramedian brainstem infarction (Leigh and Tomsak, 2004), although MRI in these patients, including ours, showed no evidence a lesion in this region, perhaps because of resolution limitations related to cellular-level dysfunction.…”
Section: Discussioncontrasting
confidence: 50%
“…That is, the saccadic eye movement is encoded by the temporal discharge of burst neurons [35]. Experimental or clinical lesions of the PPRF and riMLF abolish or slow saccades [7,11,12]. Most patients with PSP eventually show slow [24] or absent vertical saccades, and neuropathological studies have demonstrated involvement of the region in which riMLF lies [6,9].…”
Section: Discussionmentioning
confidence: 99%
“…Medium-lead burst neurons in the PPRF discharge before both horizontal and vertical saccades (21), and bilateral experimental lesions in the caudal PPRF of monkeys impair vertical rapid eye movements (visually triggered saccades and quick phases of nystagmus) (22,23). Slow voluntary saccades and loss of quick phases of vestibular and optokinetic nystagmus in both horizontal and vertical planes may result from pontine lesions involving the PPRF (24). Those findings indicate that ascending pathways from the PPRF are necessary for the generation of vertical as well as horizontal fast eye movements, but the ascending projections to the midbrain are not sufficient to generate voluntary or visually guided saccades in the face of disruption of cerebral corticofugal projections to the midbrain.…”
Section: Discussionmentioning
confidence: 98%